The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s13337-013-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of low pathogenic H9N2 avian influenza A viruses from a healthy flock and its comparison to other H9N2 isolates

Abstract: Several outbreaks of avian influenza (AI) caused by H9N2 subtype, have been reported in the poultry industry during 1990 around the globe. Currently, H9N2 are endemic in the large area of Middle and Far East, including Pakistan. Since H9N2 AI viruses are sporadically reported from humans, extensive incidence of H9N2 in poultry imposes a great risk for human health. In this context, continuous monitoring of the poultry and determining the genetic nature of these viruses are fundamental to predict any future thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…H9N2 has widely circulated in the poultry population and caused economic losses ( 34 , 35 ). This virus has low pathogenicity to birds, but it is a severe threat to public health ( 36 ). Although prevailing vaccines decrease the disease incidence in birds, they cannot completely prevent the infection and shedding of the LPAIV-H9N2 ( 14 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…H9N2 has widely circulated in the poultry population and caused economic losses ( 34 , 35 ). This virus has low pathogenicity to birds, but it is a severe threat to public health ( 36 ). Although prevailing vaccines decrease the disease incidence in birds, they cannot completely prevent the infection and shedding of the LPAIV-H9N2 ( 14 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Avian influenza virus (AIV) is divided into two groups based on their pathogenicity including highly pathogenic avian influenza (HPAI) in which mortality may be as high as 100%, and low pathogenicity avian influenza (LPAI) which causes milder respiratory disease [ 2 ]. Laboratory examinations in specific pathogen-free (SPF) chicken demonstrate that H9N2 AIV is low pathogenic [ 3 ]. It is almost one decade that the Middle East and Asian countries are facing frequent outbreaks of H9N2 infection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This sign basically supported that there is the difference in pathogenicity and various studies demonstrated diversity in prevalence of virus in this country (Fatima et al 2017;Kausar et al 2018). These isolates were found unique from the previous isolates as they differed antigenically (Munir et al 2013;Islam et al 2017). The idea gets more weightage by the fact that several H9N2 isolates are isolated from animals and humans in Southeast Asia.…”
Section: Discussionmentioning
confidence: 80%
“…H9N2 AIV is considered a low pathogenic virus as it affects only those organs which contain trypsin-like proteases that are necessary to cleave H0 into H1 and H2. This study revealed that H9N2 AIVs evolved over a while thus, generating different antigenic groups (Munir et al 2013;Chaudhry et al 2017). Potential Glycosylation sites play a key role in increased virulence of the virus, either due to change in receptor configuration or modification in patterns of antigenicity (Islam et al 2017).…”
Section: Discussionmentioning
confidence: 96%